The dynamics of price adjustment and relationships in the formal and informal beef markets in Namibia. Issue 1 (2nd January 2017) - Kalundu, Kennedy Sean; Meyer, Ferdi
ABSTRACT: Beef prices have increased significantly in Namibia in recent years. The main reason for the increase in beef producer prices is the high input cost and drought, leading to excessive culling of breeding herds among commercial farmers. Johansen multivariate test of co-integration and multivariate vector error correction model are used to investigate the price adjustment and the existence of long-run relationship among the beef prices at various stages of the value chain. The results show that the beef cattle prices are integrated and exhibit a long run relationship. Formal (for grade A) and informal (grade C) beef cattle prices suggest that they adjust to long-run equilibrium at different speeds. For instance, prices in the formal markets adjust to disequilibrium at about 81 per cent, while prices in informal markets adjust to disequilibrium at 63 per cent. Granger causality results indicates the log price of grade C beef cattle in the informal market does not cause Granger log price of grade A beef cattle in the formal market, log of wholesale beef price of grade A beef and log of export beef price of grade A unidirectional at the 1 per cent level of significance. The adjustment can be attributed to the objectives and the nature beef markets understudy, coupled to the lack of efficient price information linkages between formal and informal beef cattle markets.